Strategi Pemberdayaan Perempuan Melalui Pengajian Majelis Taklim Ibu-Ibu Masjid Agung Sunda Kelapa Kecamatan Menteng Jakarta Pusat - Tamirano, Randi; Zen, Muhammad (Hikmah, 2024)
Women are an interesting topic to be discussed anywhere and anytime without restrictions on place and time, especially regarding the education experienced by women, both general education and religious education. Women's education is a priority because women have a very important role in making decisions and influencing the lives of children and families.Empowerment is the transformation of power relations between men and women, the concept of empowerment can be understood in two contexts. First, power in the decision-making process. Second, related empowerment focuses on the relationship between women's empowerment and its impact on men in diverse communities.This research aims to find out the strategy of women's empowerment through the taklim council of the women of the Sunda Kelapa Grand Mosque. The five women's empowerment strategies used are increasing women's participation, providing religious education and expertise, providing leadership to women, increasing economic empowerment and increasing self-confidence.This study uses an interpretive research paradigm, a type of qualitative research, and a descriptive-analytical method. The results of this study show that the strategy carried out is with several activities such as teaching reading the Quran, teaching the book of figh, fostering women's faith, friendship programs, empowerment of duafa, improving the household economy, and forms of empowerment, namely intellectual, economic and spiritual empowerment. This is in accordance with the Theory of Religious Empowerment showing that the empowerment of women in the religious field at the Sunda Kelapa Grand Mosque is true.